Prediction of Effects of Geogrid Reinforced Granular Fill on the Behaviour of Static Liquefaction - A. Hemalatha; N. Mahendran; G. Ganesh Prabhu (Advances in Materials Science and Engineering)
The experimental investigation on the effects of granular fill and geogrid reinforced granular fill on the behaviour of the static liquefaction potential of the subsoil is reported in this study. A series of plate load test were carried out with different thickness of the granular fill, number of geogrid layers, and size/dimension of the footing. The test results were presented in terms of bearing capacity and subgrade modulus for the settlement of δ10, δ15, and δ20. The experimental results revealed that the introduction of granular fill significantly increases the bearing capacity and effectively control the settlement behaviour of the footing. The introduction of geogrid in granular fill enhanced the Percentage of Control in Settlement and Bearing Capacity Ratio by a maximum of 328.54% and 203.41%, respectively. The introduction of geogrid in granular fill interrupts the failure zone of the granular fill and enhances the subgrade modulus of the footing by a maximum of 255.55%; in addition subgrade modulus of the footing was increased with an increase in the number of geogrid layers. Based on the test results it is suggested that the footing with large size has beneficial improvement on the reinforced granular fill.